Sanktuaria archidiecezji poznańskiej – rola, zadania, znaczenie - Brzeziński, Maciej (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
The focus of the article are the shrines located within the present boundaries of the Poznań Archdiocese. The definition of the term “shrine” is discussed followed by deliberation of the role and significance of sacred places in the light of the canon law and the statutes of two archdiocesan synods held in 1968 and 2004-2008, respectively. A classification of the sacred places of the Poznań Archdiocese is proposed taking into consideration different scholarly criteria. The role of the custodian of a shrine and the meaning of pilgrimages and religious tourism are also presented.